2021
DOI: 10.1007/s11270-021-05215-y
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Suitable Extractant for Estimating Plant Available Arsenic in Relation to Soil Properties and Predictability by Solubility-FIAM

Abstract: Extractant for estimating plant available arsenic (As) in soil has not been universally established. Moreover, to assess and monitor the complex chemical behaviour of arsenic (As) in soil and subsequently its transfer in crops, a suitable extraction protocol considering the soil properties in relation to crop uptake is required. For this purpose, a pot experiment was conducted to evaluate the suitability of the extractants for determination of extractable As in soil and risk assessment by solubility-free ion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The problem with CaCl 2 is the presence of chloride. The existence of chloride (Cl) in nal prepared samples leads to polyatomic ions 40 Ar 35 Cl and 35 Cl 16 O formation in a smaller concentration of As in samples and hamper its determination in ICP-MS. Thus an acidbased extractant may be a suitable option for As determination in ICP-MS. Further, some studies suggested that due to higher viscosity and variation in surface tension of H 3 PO 4 and H 2 SO 4 , changes in droplet size distribution and nebulization e ciency reduce the signal intensity in ICP-OES (Yoshimura et al, 1990).…”
Section: Arsenic Extracted With Different Extractantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem with CaCl 2 is the presence of chloride. The existence of chloride (Cl) in nal prepared samples leads to polyatomic ions 40 Ar 35 Cl and 35 Cl 16 O formation in a smaller concentration of As in samples and hamper its determination in ICP-MS. Thus an acidbased extractant may be a suitable option for As determination in ICP-MS. Further, some studies suggested that due to higher viscosity and variation in surface tension of H 3 PO 4 and H 2 SO 4 , changes in droplet size distribution and nebulization e ciency reduce the signal intensity in ICP-OES (Yoshimura et al, 1990).…”
Section: Arsenic Extracted With Different Extractantsmentioning
confidence: 99%
“…Some reports have correlated bioaccessible As with in-vitro analysis or human oral bioaccessibility of As (Bari et al, 2021;Li et al, 2015;Fernández-Caliani et al, 2019). A few studies have set out to derive relationships between forms of As in soils and plant As content (Raj et al, 2021;Yu et al, 2016). Therefore, a suitable analytical approach is necessary to assess readily available forms of As in soil.…”
Section: Introductionmentioning
confidence: 99%
“…There are both direct and indirect evidences to suggest that As is held in soils by sediments by oxides (e.g. of Fe, Mn, Zn) through the formation of inner-sphere complexes via ligand exchange mechanism (Kumari et al, 2021;Raj et al, 2021). Iron appeared highly efficient to sequester As and to restrict As acquisition by rice (Chowdhury et al, 2018a).…”
Section: Tablementioning
confidence: 99%
“…Arsenic in soil is present in both the solution and solid phases. The As may be in the form of organic and inorganic complexes (present in soil solution), adsorbed ions and compounds (clay and organic colloids), bound to secondary minerals and precipitated oxides of iron (Fe) and manganese (Mn), carbonates, and phosphates or complexed with organic matter and free ions (Raj et al., 2021). Total elemental concentrations within the soil offer little insight into the potential bioavailability of the elements (such as As), which may cause metal(loid) sequestration and recycling within the soil environment under the influence of various soil parameters (Kumari et al., 2021).…”
Section: Introductionmentioning
confidence: 99%